The Effectiveness of Group Guidance Services with Self-Management Techniques to Improve Learning Discipline of Class XI Science Students of SMA Negeri 6 Palu - Silvianingsi Silvianingsi; Ridwan Syahran; Bau Ratu; Munifah Munifah (FKIP - Universitas Riau, 2026)
Learning discipline is an important factor in supporting students’ academic success. However, many high school students still experience disciplinary problems, such as coming late to school, studying irregularly, and showing low responsibility in completing assignments. To address these issues, guidance and counseling teachers can provide group guidance services using self-management techniques to help students develop better self-regulation and learning habits. This study aimed to determine the effectiveness of group guidance services with self-management techniques in improving the learning discipline of Grade XI science students at SMA Negeri 6 Palu. The study employed a quantitative approach with a quasi-experimental method using a Non-Equivalent Control Group Design. The sample consisted of 12 students who were divided into an experimental group and a control group, with six students in each group. Data were collected using a learning discipline questionnaire administered before and after the intervention. The data were analyzed using the Mann Whitney U test. The findings revealed a significance value of 0.004 (p < 0.05), indicating a significant difference between the experimental and control groups. Students in the experimental group showed a greater improvement in learning discipline than those in the control group.